1976
DOI: 10.1099/00221287-96-2-341
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Neisseria gonorrhoeae Grown in vivo to Ingestion and Digestion by Phagocytes of Human Blood

Abstract: S U M M A R YAttempts to study quantitatively the phagocytosis of gonococci from urethral pus failed because of the small numbers of organisms and technical difficulties. However, gonococci from chambers implanted subcutaneously in guinea pigs, which were similar to gonococci from urethral pus in their resistance to killing by human serum, were obtained in sufficient quantities for comparison in phagocytosis tests with the in vitro grown strain from which they were derived.Microscopic and viable counts of gono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 14 publications
3
26
0
Order By: Relevance
“…Thus, the selection of variants with particular opacity-related proteins is in accord with previous observations that guinea-pig chamber gonococci were antigenically distinct from the same strain grown on laboratory media (Penn et al, 1978) and showed enhanced resistance to host defences Witt et al, 1976). The results from the present study demonstrate that additional, presumably antigenic, proteins are indeed present in gonococci obtained from guinea-pig chambers and that these can be maintained by careful colony typing during growth in vitro.…”
Section: H M M C B R I D E a N D O T H E R Ssupporting
confidence: 79%
“…Thus, the selection of variants with particular opacity-related proteins is in accord with previous observations that guinea-pig chamber gonococci were antigenically distinct from the same strain grown on laboratory media (Penn et al, 1978) and showed enhanced resistance to host defences Witt et al, 1976). The results from the present study demonstrate that additional, presumably antigenic, proteins are indeed present in gonococci obtained from guinea-pig chambers and that these can be maintained by careful colony typing during growth in vitro.…”
Section: H M M C B R I D E a N D O T H E R Ssupporting
confidence: 79%
“…In all three experiments the killing of mycoplasmas grown in vivo by macrophages was significantly less than that of organisms grown in vitro; this difference did not appear to depend on the numbers of mycoplasmas attached to the macrophages at the start of the experiment. Possible explanations for these differences are (1) that the uptake of both mycoplasma preparations by macrophages is the same, but the intracellular killing of in-vivo-grown organisms is less efficient as seen for in-vivo-grown Neisseria gonorrhoeae in human phagocytes (Witt et al, 1976); (2) that there may be changes in the antigenic structure of mycoplasmas replicating in vivo, or (3) that host material or non-opsonic antibody or both may be bound to the mycoplasma and inhibit the attachment of opsonic antibody to the organism. There is some evidence that mycoplasmas can selectively "acquire" host antigens, and these may hinder their recognition by the host's defence mechanisms (Wise, Cassell and Acton, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…However, not all investigators have been able to demonstrate such antibody (Roberts, 1977). Furthermore, apparent survival of gonococci inside phagocytic cells has been reported (Evans, 1977;Witt et al, 1976) suggesting that phagocytosis might occasionally lead to a focus for persistent infection.…”
Section: Introductionmentioning
confidence: 99%